Secularism the basics - Berlinerblau, Jacques 1966- (Abingdon, Oxon New York, NY Routledge, 2022)
"Secularism: The Basics is a concise and engaging introduction to confusing and contradictory public discussions of secularism across the globe. "Secularism" must be the most confused and convoluted term in the entire global political lexicon. From New York, to Paris, to Istanbul, to Addis Ababa, to New Delhi, to Montevideo, there are countless examples of politicians, religious leaders and journalists, invoking the S-word in heated debates about public education, gender, sex, national symbols, and artistic freedom. In this lively and lucid book, Jacques Berlinerblau addresses why secularism is defined in so many ways and why it so ignites people's passions. In so doing, he explores the following important questions: What does secularism mean? Why should we care about this idea? What are the different types of secularism and what are their histories? What are the basic principles of political secularisms? Why are secularism and Atheism often confused? What is the relationship between secularism and LGBTQ rights? What opposition are secularisms up against? What does the future hold for a concept millennia in the making, but only really operationalized in the twentieth century? With a glossary of key terms, case studies, informative tables, and suggestions for further reading throughout, the book considers key philosophical, religious, anti-religious, post-modern and post-colonial arguments around secularism. This book is an ideal starting point for anyone seeking a readable introduction to the often-conflicting interpretations of one of our era's most complex and controversial ideas. Jacques Berlinerblau is Professor of Jewish Civilization in the Walsh School of Foreign Service at Georgetown University, USA. He is the author of numerous books and scholarly articles on secularism"--
Includes bibliographical references and index
Keywords: Secularism